2021
DOI: 10.1002/14651858.cd010837.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testing for cancer on cancer- or venous thromboembolism (VTE)-related mortality and morbidity in people with unprovoked VTE

Abstract: This is a repository copy of Effect of testing for cancer on cancer-or venous thromboembolism (VTE)-related mortality and morbidity in people with unprovoked VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Although cancer is a relevant risk factor, a Cochrane meta-analysis found no evidence for additional PET/CT testing after a first unprovoked VTE because there was no benefit in any outcomes: cancer and all-cause mortality ( P =0.25 and P =0.66, respectively), VTE-related morbidity ( P =0.96), time to cancer diagnosis ( P =0.88), and malignancy diagnosis in the early or advanced stage ( P =0.36 and P =1.00, respectively). 72…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…Although cancer is a relevant risk factor, a Cochrane meta-analysis found no evidence for additional PET/CT testing after a first unprovoked VTE because there was no benefit in any outcomes: cancer and all-cause mortality ( P =0.25 and P =0.66, respectively), VTE-related morbidity ( P =0.96), time to cancer diagnosis ( P =0.88), and malignancy diagnosis in the early or advanced stage ( P =0.36 and P =1.00, respectively). 72…”
Section: Venous Thromboembolism (Deep Vein Thrombosis and Pulmonary E...mentioning
confidence: 99%
“…However, a meta-analysis of four randomized controlled trials has concluded that extensive cancer screening following VTE, including CT scans or combined positron emission tomography/CT scans, results in detection of cancers at an earlier stage, but does not reduce cancer-related mortality compared with routine screening (i.e., current guidelines). 41 Consequently, no current evidence proposes extensive cancer screening following a VTE diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The large heterogeneity of solid and hematologic cancer distribution after acute VTE accounts for difficulties in targeting organ-specific cancers in current screening strategies. However, most studies have failed to show any benefit for overall morbidity and mortality despite a higher number of initially detected cancers, possibly at an earlier stage [ 11 ]. As such, current guidelines recommend limited assessment (medical history, physical examination, laboratory tests, chest X-ray) associated with age- and sex-specific procedures (mammography between 50 and 75 years old, cervical Pap test in women aged 21–65 years, FOBT in individuals aged 50–75 years, PSA or prostate examination in men aged 55 to 70 years and low-dose thoracic CT for smokers aged more than 55 years old).…”
Section: Discussionmentioning
confidence: 99%
“…However, the SOME trial, comparing a limited screening to an extensive approach, including an abdominal CT associated with a virtual colonoscopy and gastroscopy, did not improve cancer detection or prognosis [ 10 ]. To date, although extensive screening procedures have been associated with a higher number of detected cancers, their impact on survival seems uncertain [ 11 ]. As such, all recent guidelines favor limited screening, but current real-life clinical practices are mainly based on individual screening strategies according to the physician’s choice [ 5 ].…”
Section: Introductionmentioning
confidence: 99%